A Review of Sex Differences in Peer Relationship Processes: Potential Trade-offs for the Emotional and Behavioral Development of Girls and Boys - Rose, Amanda J. (2006)
Theory and research on sex differences in adjustment focus largely on parental, societal, and biological influences. However, it also is important to consider how peers contribute to girls’ and boys’ development. This paper provides a critical review of sex differences in: several peer-relationship processes, including behavioral and social-cognitive styles, stress and coping, and relationship provisions. Based on this review, a speculative peer-socialization model is presented that considers the implications of these sex differences for girls’ and boys’ emotional and behavioral development. Central to this model is the idea that sex-linked relationship processes have costs and benefits for girls’ and boys’ adjustment. Finally, we present recent research testing certain model components and propose approaches for testing understudied aspects of the model.